Applicability of a clinical scoring criteria for disease severity of ß-thalassemia/hemoglobin E in Indonesia (Medical Journal of Indonesia, 2018)
Background: β-thalassemia/HbE presents with a variety of clinical symptoms, from asymptomatic to severe, requiring routine transfusion. However, there is currently no agreed classification system to stratify patients based on clinical severity of β-thalassemia/HbE in the Indonesian population. Thailand has already established a classification system, and this study aimed to identify the applicability of the Thailand clinical scoring criteria to determine the severity of β-thalassemia/HbE in the Indonesian population.Methods: This descriptive study was conducted by evaluating patients with β-thalassemia/HbE, who were classified into mild, moderate, or severe groups based on the Thailand clinical scoring criteria.Results: A total of 293 subjects with β-thalassemia/HbE were included. Based on this clinical scoring criteria, it was found that only 21.5% of patients were classified as mild, and the remaining 35.5% and 44% were classified as moderate and severe respectively. Approximately 68.2% of the subjects in the severe group received transfusion at <4 years old, while only 10% of those in the mild group were transfused at the same age. In the mild group, only 10% of the subjects underwent routine transfusion, compared to 98.4% of the subjects in the severe group. In addition, only 27% of the subjects in the mild group showed stunted growth, while that in the moderate and severe groups were 54.5% and 86.8%, respectively.Conclusion: Thailand clinical scoring criteria is able to determine the severity of Indonesia thalassemia patient which needs further management, i.e. transfusion and observation of stunted growth. This scoring system will help provide the provision of the most ideal management for the groups of patients based on their requirements.